SOLUBILITY AND DESTRUCTION OF OIL IN SEA WATER - A. S. Abdusamadov; A. P. Panarin; A. K. Magomedov; L. D. Kovalenko; B. R. Guseinova; A. M. Dokhtukaeva; L. A. Dudurkhanova (Юг России: экология, развитие)
The solubility and the destruction of crude oil in seawater in conditions of the Caspian sea have been studied.